A = b is given to us
Multiply both sides by c to get
a = b
a*c = b*c
The rule to multiply both sides by c is the multiplicative property of equality
Then on the right side, replace c with d. This replacement is possible due to the fact that c = d. This is using the substitution property.
So we go from
a*c = b*c
to this
a*c = b*d
That it is 4,6090 because when u divide that ,400 by 2,400 u will get 4,000
Answer:
Step-by-step explanation:
f(x) = 2x^3 - 4x.....find f(-2).....so sub in -2 for x
f(-2) = 2(-2^3) - 4(-2)
f(-2) = 2(-8) + 8
f(-2) = -16 + 8
f(-2) = -8 <==
Answer:
3.
Step-by-step explanation:
The graph is being moved to the left and then stretched by a factor of three. If it were to be compressed than the 3 would be 1/3.